2014
DOI: 10.1021/ol501423t
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Total Synthesis of Salvileucalin C

Abstract: A concise and efficient approach for the diastereoselective total synthesis of salvileucalin C, as well as their biosynthetically related diterpenoids salvileucalin D, salvipuberulin, isosalvipuberulin, and dugesin B, has been reported for the first time. The key features of the strategy are based on a Beckwith-Dowd ring expansion, a tandem diastereoselective Stille coupling/debromination/desilylation/lactonization reaction, and a photoinduced electrocyclic ring contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Considering the unusual regioselectivity of the reaction carried out in the aqueous solvents and its usefulness in the synthesis of subsituted αbutenolides [2,15] further studies on the reaction mechanism are performing in our laboratory. This efficient protocol offers a facile access to α-substituted α,β-unsaturated-γ-lactones with excellent regiocontrol and stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the unusual regioselectivity of the reaction carried out in the aqueous solvents and its usefulness in the synthesis of subsituted αbutenolides [2,15] further studies on the reaction mechanism are performing in our laboratory. This efficient protocol offers a facile access to α-substituted α,β-unsaturated-γ-lactones with excellent regiocontrol and stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that water plays significant impact on the regioselective Mukaiyama aldol reaction between cyclic dienol silanes and aromatic aldehydes or ketoesters . This new attempt was demonstrated also by other authors as a highly regioselective route to α‐substituted furan derivatives, but even more appreciated diastereoselective variant of this methodology have not yet been realized. Herein, we report the utility of these concept by documenting the first diastereoselective catalytic aqueous Mukaiyama aldol reaction as an alternative method for efficient construction of α‐substituted 2( 5H )‐furanone moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Various α‐substituted α,β‐unsaturated‐γ‐lactones were obtained from a range of aldehydes in good yields and enantioselectivities by simply tuning the solvent used. Synthetic utility of our concept was recently demonstrated by Ding in the diastereoselective total synthesis of Selvileucelin C …”
Section: Introductionmentioning
confidence: 85%
“…During this cascade cyclization an isomer with trisub-stituted olefin was also formed in 11 % yield which was generated due to the rearrangement of the exocyclic olefin of compound 122. In 2014, Ding et al [39] published the total synthesis of diterpenoids salvileucalin C (126) and salvileucalin D (127) where Heck cyclization was adopted for the construction of [5,5]-bicycle scaffold (Scheme 12). Intramolecular Heck cyclization of 124 proceeded smoothly to produce intermediate 125 in 76 % yield under the optimized conditions like Pd-(Ph 3 P) 2 Cl 2 , 1,2,2,6,6-pentamethylpiperidine (PMP) in DMF.…”
Section: Diterpenementioning
confidence: 99%